Strengthening of District/Taluk level hospitals through implementation of post-graduate medical courses in Karnataka, India - Parimala S Maroor; B S Pushpalatha; Sangeetha Kodkani; Lourdu Shruthi; Damaraju Ashwini; Anjali Sharma; Himanshu Negandhi; Suresh S Shapeti; Sanjay P Zodpey (Wolters Kluwer Medknow Publications, 2024)
The World Health Organization (WHO) recommends the requirement of human resource for health (HRH) stands at 44.5 skilled health workers per 10,000 population. WHO recognizes India as one of the countries which has HRH crisis. Karnataka, a southern state in India, has the highest number of medical colleges yet faces the shortage of specialists in the public hospitals. We conducted desk review to understand the HRH crisis, particularly the medical specialists in India. Simultaneously, we conducted secondary research to explore the initiatives taken by the Government of Karnataka (GoK) to mitigate the shortage of medical specialists in the rural areas. GoK scaled up the National Board of Examination in Medical Sciences (NBEMS) postgraduate and super-speciality courses such as Diplomate of National Board (DNB), Diploma, and Doctorate of National Board (DrNB) in district hospitals (minimum 250-500 bedded) and taluk hospitals (minimum 100 bedded) by utilizing the existing resources. Karnataka is the first state in India to expand the NBEMS (DNB and Diploma) courses in taluk hospitals and to begin DrNB courses in district hospitals. The paper documents the process of implementation of the NBEMS courses at district and taluk hospitals of Karnataka, which has supported in strengthening these hospitals in the state.